DIGITAL MARKETING TOOLS FOR THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES IN THE GLOBAL MARKET - SEROV, Volodymyr; KOROL, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the primary digital marketing tools that foster the development of agricultural enterprises in the global market. It analyzes the advantages and potential of utilizing social media, SEO optimization, e-commerce, content marketing, and analytical tools to strengthen agricultural companies’ competitiveness. Each tool is characterized by its role in building effective communication with consumers, increasing brand awareness, and fostering customer loyalty. Examples of successful social media applications illustrate how they can establish direct connections with customers and increase engagement with products. Recommendations are proposed for the comprehensive integration of digital tools into the marketing strategies of agricultural enterprises. These include content adaptation for SEO, personalized email campaigns, and analytics applications for monitoring customer behavior. The feasibility of using CRM systems to automate marketing processes is substantiated, as these systems improve customer interaction management, enhance responsiveness to market changes, and facilitate the development of long-term partnerships. In an increasingly digitalized world, the agricultural sector is adapting its marketing approaches to engage consumers and remain competitive globally. Social media, in particular, has become a powerful tool for creating direct connections between agricultural enterprises and their customers. Platforms like Facebook, Instagram, and LinkedIn allow companies to share product information, showcase sustainability practices, and foster a community around their brand. Studies show that effective use of social media can increase customer engagement by as much as 30%, helping companies build stronger relationships and improve retention. SEO optimization is another essential element of digital marketing in agriculture. It allows companies to enhance their visibility on search engines. By incorporating relevant keywords and improving website structure, agricultural enterprises can ensure that potential customers find their products more efficiently. Research indicates that companies with high search engine rankings receive over 60% more organic traffic, translating to a steady flow of prospective clients.